2019
DOI: 10.1186/s13058-019-1125-0
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β regulates epithelial-mesenchymal transition and cancer stem cell properties in triple-negative breast cancer

Abstract: Background Triple-negative breast cancers (TNBCs), which lack receptors for estrogen, progesterone, and amplification of epidermal growth factor receptor 2, are highly aggressive. Consequently, patients diagnosed with TNBCs have reduced overall and disease-free survival rates compared to patients with other subtypes of breast cancer. TNBCs are characterized by the presence of cancer cells with mesenchymal properties, indicating that the epithelial to mesenchymal transition (EMT) plays a major role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 62 publications
2
75
0
Order By: Relevance
“…In agreement with earlier observations (Lee and Ro, 2015;Vijay et al, 2019), pharmacological inhibition of GSK3β resulted in SLUG downregulation in basal-like breast cancer cell lines and prevented EMT in cells treated with TGF-β. These observations suggest that inhibition of GSK3β drives mammary cell differentiation, and that it may be a promising strategy for the treatment of basallike breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with earlier observations (Lee and Ro, 2015;Vijay et al, 2019), pharmacological inhibition of GSK3β resulted in SLUG downregulation in basal-like breast cancer cell lines and prevented EMT in cells treated with TGF-β. These observations suggest that inhibition of GSK3β drives mammary cell differentiation, and that it may be a promising strategy for the treatment of basallike breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…HME cells have been routinely used as a model system to study the oncogenic transformation of non-immortalised breast epithelial cells to immortalised transformed cancer cells. [25][26][27] Furthermore, HME cells lack expression of the oestrogen receptor (ER) and therefore provides the opportunity to model the development of ER-negative breast cancers. 28 A more recent study showed that the phenotype and cellular behaviour that emerged in a separate model of MYC expressing HME cells was very similar to that of MDA-MB-231 cells, a TNBC cell line.…”
Section: Generation Of Hme Cells Expressing Tert Myc or Her2mentioning
confidence: 99%
“…Various important metastasis-and cancer-related pathways were enriched, including cell cycle regulation, angiogenesis, EMT, and Wnt, TGFβ and ESR1-mediated signaling. Speci cally, we found that these miRNAs participate in these pathways through interactions with targets such as ESR1, GSK3β, MMP-2/-9, TGFβ, mTOR, SMAD4, c-Myc, HIF1α, and PI3KCA, some of which have been shown to regulate various signaling pathways and cellular functions in breast carcinogenesis (47)(48)(49)(50). These results suggest that these miRNAs target many key genes and work as a module, contributing to breast cancer phenotypic differences and aggressiveness.…”
Section: Discussionmentioning
confidence: 68%